Vitiligo Review: etiopathogenesis, diagnosis and treatment - Witek, Aleksandra; Parys, Jakub; Mikosińska, Agnieszka; Kaźmierczak, Martyna; Mossakowski, Maciej; Kałuziak, Patrycja; Jajczak, Marta; Litwin, Mateusz; Jesionek, Stanisław; Bieś, RAfał (Quality in Sport, 2025)
Introduction and purpose:This review is intended for healthcare professionals, including dermatologists, primary care physicians, and researchers, who seek a comprehensive understanding of vitiligo. It is also relevant for patients and their families to better understand the condition. The review is indicated for those dealing with cases of vitiligo that are difficult to diagnose or manage, those with widespread or refractory vitiligo, and individuals interested in the latest advancements in treatment. The purpose of this review is to provide a detailed analysis of vitiligo’s etiopathogenesis, the current diagnostic methods, and the most effective treatment options. By exploring the genetic, autoimmune, and environmental factors involved in vitiligo, the review aims to enhance the understanding of the disease's origin and progression. Additionally, it seeks to offer evidence-based insights into the most up-to-date diagnostic tools and therapeutic approaches, ultimately improving patient care and guiding future research directions. State of knowledge: Vitiligo is an autoimmune disorder characterized by the loss of melanocytes, leading to depigmented skin patches. Its exact cause remains unclear, but genetic and environmental factors, such as stress and skin trauma, are thought to contribute. Diagnosis is primarily clinical, with dermoscopy and biopsy used in uncertain cases. While treatments like topical corticosteroids, phototherapy, and JAK inhibitors are effective for some, no cure exists, and responses vary widely. Surgical options like melanocyte transplantation can help with localized cases. Ongoing research aims to better understand the disease mechanisms and improve treatment outcomes.